2000
DOI: 10.1046/j.1537-2995.2000.40111414.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor neutrophil function after plateletpheresis

Abstract: Neutrophil function was altered after apheresis, although to a very small extent, and contact between neutrophils and the foreign surface in the apheresis systems is found to be a biotolerant procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…insignificant increase in absolute monocyte, lymphocyte subsets count, and WBC count. This was partially in agreement with Western and Videm reported an insignificant change in the donors mean leukocyte counts [31]. In contrast; Prior and coworkers found a transient drop in the absolute lymphocyte counts and T cells in healthy cytapheresis donors (mostly regular donors) during cardiopulmonary bypass [32].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…insignificant increase in absolute monocyte, lymphocyte subsets count, and WBC count. This was partially in agreement with Western and Videm reported an insignificant change in the donors mean leukocyte counts [31]. In contrast; Prior and coworkers found a transient drop in the absolute lymphocyte counts and T cells in healthy cytapheresis donors (mostly regular donors) during cardiopulmonary bypass [32].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we found that the expression of (CD11c & CD42a), (CD61), (CD11c), (IgG1) and (IgG2) postdonation was significantly increased on monocytes but with insignificant changes in the expression of (CD11c & CD42a), (CD61), and (CD11c) on neutrophil. However, there were significant increase in post donation expression of (IgG1 & IgG2a) and (IgG2a & CD41) on both monocytes and neutrophil, this was in agreement with Western and Videm [31] who found slight neutrophil function change after apheresis owing to contact between neutrophils and the apheresis foreign surface found to be a bio-tolerant procedure and also in agreement with Ahn and coworkers who established that activated platelets bind preferably to monocytes to form the plateletmonocyte complex (PMCs) [34]. This can be explained by the fact that during the apheresis procedure, the donor blood was exposed to an artificial membrane and external forces such as centrifugation that might activate platelets and leukocytes [35].…”
Section: Discussionsupporting
confidence: 85%
“…Although, there was a significant increase in postdonation expression of (IgG1 and IgG2a) and (IgG2a and CD41) on both monocytes and neutrophil. 21,22 Rinder et al showed that the modification of lymphocyte count was reached to normal level within 3 days after the extracorporeal process. 23 However, we had not assessed neutrophil, lymphocyte, and monocyte but observed WBC increasing by Trima Accel and MCS+, and CD4, CD25, and TGF-beta gene were not significantly different in the two devices.…”
Section: Discussionmentioning
confidence: 99%
“…in the investigation of transfusion-related acute lung injury (TRALI), in population studies or in the analysis of potential changes during pregnancy [122][123][124][125][126][127]. Moreover, functional and morphologic changes of circulating neutrophil cells during plateletpheresis were investigated using flow cytometry [128]. Such investigations were also performed to identify the optimal storage conditions for granulocytes [129].…”
Section: Granulocyte/monocyte Integrity and Immunologymentioning
confidence: 99%